The South Atlantic Meridional Overturning Circulation and Mesoscale Eddies in the First GO‐SHIP Section at 34.5°S. Issue 2 (7th February 2021) - Manta, G.; Speich, S.; Karstensen, J.; Hummels, R.; Kersalé, M.; Laxenaire, R.; Piola, A.; Chidichimo, M. P.; Sato, O. T.; Cotrim da Cunha, L.; Ansorge, I.; Lamont, T.; et al.
Abstract: The variability of the Atlantic meridional overturning circulation (AMOC) has considerable impacts on the global climate system. Past studies have shown that changes in the South Atlantic control the stability of the AMOC and drive an important part of its variability. That is why significant resources have been invested in a South (S)AMOC observing system. In January 2017, the RV Maria S. Merian conducted the first GO‐SHIP hydrographic transect along the SAMOC‐Basin Wide Array (SAMBA) line at 34.5°S in the South Atlantic. This paper presents estimates of meridional volume, freshwater (MFT), and heat (MHT) transports through the line using the slow varying geostrophic density field and direct velocity observations. An upper and an abyssal overturning cell are identified with a strength of 15.64 ± 1.39 Sv and 2.4 ± 1.6 Sv, respectively. The net northward MHT is 0.27 ± 0.10 PW, increasing by 0.12 PW when we remove the observed mesoscale eddies with a climatology derived from the Argo floats data set. We attribute this change to an anomalous predominance of cold core eddies during the cruise period. The highest velocities are observed in the western boundary, within the Brazil and the Deep Western Boundary currents. These currents appear as a continuous deep jet located 150 km off the slope squeezed between two cyclonic eddies. The zonal changes in water masses properties and velocity denote the imprint of exchange pathways with both the Southern and the Indian oceans. Plain Language Summary: The Atlantic meridional overturning circulation (AMOC) is a crucial element of the global ocean circulation and climate. It connects the Southern Ocean to the northern North Atlantic, and is responsible for the interhemispheric northward transport of heat and freshwater. The South Atlantic is a crossroad for water masses from the Southern, the Indian and the North Atlantic oceans. This paper analyzes the first full‐ocean‐depth trans‐basin measurements of the southernmost enclosed section of the Atlantic between South Africa and Brazil along 34.5°S. Our results confirm a northward transport of heat at this latitude. We also found a complex water mass structure and dynamics, characterized by intense boundary currents and mesoscale eddies. It is the sum of these elements that is not only crucial for the Atlantic but also for the global ocean circulation and climate. Key Points: Overturning maximum is 15.64 ± 1.39 Sv; Meridional heat and freshwater transport are 0.27 ± 0.10 PW and 0.23 ± 0.02 Sv, respectively Excluding the mesoscale eddies from the section increased the meridional heat transport by 0.12 PW The distribution of water masses and currents reflects the favorable position of the section for observing